GALINDO HERVÁS, Alfonso (2021). Historia y conceptos políticos. Una introducción a Reinhart Koselleck. Pamplona: EUNSA. 176. pp. - Enrique Ujaldón Benitez (Daimon)
RESEÑA de: GALINDO HERVÁS, Alfonso (2021). Historia y conceptos políticos. Una introducción a Reinhart Koselleck. Pamplona: EUNSA. 176. pp.